Linguistic and Cultural Approach in the Process of Teaching a Foreign Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the features of the linguistic and cultural approach to teaching a foreign language. The teacher's task is to interest the student in learning a foreign language, to acquaint him with the culture and history of the country of the language being studied. Nowadays, the linguistic and cultural approach to teaching a foreign language is in great demand, because the language is most fully assimilated against the background of culture. The implementation of the linguistic and cultural approach in foreign language classes stimulates interest in its study among students, contributes to the expansion of their horizons and motivates for further self-study.